Sustainable Cities: A Systematic Review from 2015 to 2020 (LACCEI, 2024)
In history, the formation of sustainable cities has been vital for people in different parts of the world. The aim of this study is to identify the factors that determine the sustainable development of cities. A systematic review covering the period from 2015 to 2020 was carried out in Ebsco, Proquest and ScienceDirect databases. In the methodological aspect, the eligibility and selection criteria of the studies established by the PRISMA method were taken into consideration. Thirty articles were selected from a total of 266. The results show that the largest amount of research is developed in Asia (36.7%) and the most representative sustainable development factors are economic development, social development and the level of human quality of life. Among the conclusions, it is highlighted that sustainable cities are still underdeveloped worldwide, however, there has been an increase in studies related to sustainable cities in recent years.